Abdominal Radical Trachelectomy for Early-Stage Cervical Cancer During Pregnancy: A Provocative Surgical Approach. Overview of the Literature and a Single-Institute Experience. Issue 9 (1st November 2018) - Rodolakis, Alexandros; Thomakos, Nikolaos; Sotiropoulou, Maria; Kypriotis, Konstantinos; Valsamidis, Dimitrios; Bourgioti, Charis; Moulopoulou, Lia Evangelia; Vlachos, Georgios; Loutradis, Dimitrios
Abstract : Objective: Treatment of pregnancy complication due to malignancy of the cervix constitutes a great clinical challenge between optimal maternal therapy and fetal viability. Radical trachelectomy in early-stage cervical cancer during pregnancy instead of radical hysterectomy presents an alternative approach that can offer a satisfactory outcome for the mother and fetus. Materials and Methods–Results: A literature search of articles in English has been performed. Until now, 28 women with cervical cancer, including 2 who were managed and treated in our institute, who underwent a radical trachelectomy during pregnancy have been reported. We overviewed a total of 13 abdominal trachelectomies, 13 vaginal trachelectomies, and 2 laparoscopic trachelectomies. Conclusions: Radical trachelectomy can widen the therapeutic approach of early-stage cervical cancer in pregnant women who wish to preserve their pregnancy, providing a possibility of receiving the proper treatment with no delay.